2018
DOI: 10.1016/j.ajoc.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomography-assisted retrocorneal fibrous membrane biopsy and excision

Abstract: PurposeWe report a case of retrocorneal fibrous membrane (RCFM) formation following penetrating keratoplasty (PK) and intraoperative optical coherence tomography (OCT)-guided excision of this membrane.ObservationsA 68-year-old woman with primary open angle glaucoma and corneal decompensation of the right eye secondary to tube shunt presented for 3-month follow-up of PK. On examination of the right eye, the patient was noted to have a glassy pupillary membrane with traction on the iris. Anterior segment OCT con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Intracorneal pathology can also be precisely isolated and located for biopsy using iOCT [49]. Ruland et al [50] showed that iOCT was helpful for the identification and excision of retrocorneal fibrous membranes following PK. In cases of acute corneal hydrops in keratoconus, iOCT facilitated the micropuncture of intrastromal fluid pockets combined with compression sutures and gas tamponade, which resulted in immediate reattachment of DM [33].…”
Section: Corneal Trauma and Other Cornealmentioning
confidence: 99%
“…Intracorneal pathology can also be precisely isolated and located for biopsy using iOCT [49]. Ruland et al [50] showed that iOCT was helpful for the identification and excision of retrocorneal fibrous membranes following PK. In cases of acute corneal hydrops in keratoconus, iOCT facilitated the micropuncture of intrastromal fluid pockets combined with compression sutures and gas tamponade, which resulted in immediate reattachment of DM [33].…”
Section: Corneal Trauma and Other Cornealmentioning
confidence: 99%
“…Intraoperativní OCT (iOCT) se využívá při operacích na předním i zadním segmentu oka. V předně segmentové chirurgii ho lze použít při celé řadě výkonů, zejména při penetrujících, lamelárních a endoteliálních keratoplastikách [1][2][3][4][5][6][7][8][9][10][11][12], při operacích glaukomu [13], katarakty [1,[14][15][16] a biopsiích tkání [1,[17][18]. V zadně segmentové chirurgii se využívá během pars plana vitrektomie (PPV) k řešení sklivcových a sítnicových patologií.…”
Section: úVodunclassified
“…Zemba et al [11] haben RCM wie folgt unterteilt: 1) epitheliale, 2) fibröse, 3) inflammatorische, 4) aus verbliebener Empfänger-Descemet-Membran entstehende [8] und 5) aus Transplantat-Descemet-Membran-Ablösung entstehende RCMs.…”
Section: Infoboxunclassified